Phloem development in nematode-induced feeding sites: the implications of auxin and cytokinin - Absmanner, Birgit; Stadler, Ruth; Hammes, Ulrich Z. (Frontiers in Plant Science, 2013)
Sedentary plant parasitic nematodes such as root-knot nematodes and cyst nematodes induce giant cells or syncytia, respectively, in their host plant's roots. These highly specialized structures serve as feeding sites from which exclusively the nematodes withdraw nutrients. While giant cells are symplastically isolated and obtain assimilates by transporter-mediated processes syncytia are massively connected to the phloem by plasmodesmata. To support the feeding sites and the nematode during their development, phloem is induced around syncytia and giant cells. In the case of syncytia the unloading phloem consists of sieve elements and companion cells and in the case of root knots it consists exclusively of sieve elements. We applied immunohistochemistry to identify the cells within the developing phloem that responded to auxin and cytokinin. Both feeding sites themselves did not respond to either hormone. We were able to show that in root knots an auxin response precedes the differentiation of these auxin responsive cells into phloem elements. This process appears to be independent of B-type Arabidopsis response regulators. Using additional markers for tissue identity we provide evidence that around giant cells protophloem is formed and proliferates dramatically. In contrast, the phloem around syncytia responded to both hormones. The presence of companion cells as well as hormone-responsive sieve elements suggests that metaphloem development occurs. The implication of auxin and cytokinin in the further development of the metaphloem is discussed.